2018
DOI: 10.1055/a-0573-9431
|View full text |Cite
|
Sign up to set email alerts
|

Das Usher-Syndrom, eine Ziliopathie des Menschen

Abstract: The human Usher syndrome (USH) is a complex, rare disease manifesting in its most common form of inherited deaf-blindness. Due to the heterogeneous manifestation of the clinical symptoms, three clinical types (USH1-3) are distinguished according to the severity of the disease pattern. For a correct diagnosis, in addition to the auditory tests in early newborn screening, ophthalmological examinations and molecular genetic analysis are important. Ten known USH genes encode proteins, which are from heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…To date, about 170 loci and 117 genes (36 autosomal dominant (AD), 65 autosomal recessives (AR), 11 AD/AR, and 5 X-linked genes) have been reported as causative of Non-Syndromic Hearing Loss (NSHL) (Hereditary Hearing Loss Homepage; http://hereditaryhearingloss.org/), and more than 400 syndromes associated with hearing loss and other symptoms (Syndromic Hearing Loss-SHL) have been described [6]. In particular, among the syndromes identified so far, some of them appear more frequently than the others (e.g., Usher syndrome compared to Waardenburg syndrome) [7,8]), although, in some cases, the full spectrum of clinical features might be subtle, or even not present until later in life [9].…”
Section: Introductionmentioning
confidence: 99%
“…To date, about 170 loci and 117 genes (36 autosomal dominant (AD), 65 autosomal recessives (AR), 11 AD/AR, and 5 X-linked genes) have been reported as causative of Non-Syndromic Hearing Loss (NSHL) (Hereditary Hearing Loss Homepage; http://hereditaryhearingloss.org/), and more than 400 syndromes associated with hearing loss and other symptoms (Syndromic Hearing Loss-SHL) have been described [6]. In particular, among the syndromes identified so far, some of them appear more frequently than the others (e.g., Usher syndrome compared to Waardenburg syndrome) [7,8]), although, in some cases, the full spectrum of clinical features might be subtle, or even not present until later in life [9].…”
Section: Introductionmentioning
confidence: 99%
“…How- ever, an increasing body of evidence has indicated that both homozygotes and compound heterozygous for the p.V37I variant were associated with mild to moderate hearing impairment [16,17]. The MYO7A gene encodes the actin-based motor protein myosin-VIIa, which is especially crucial for the function of cochlear hair cells and eye development [18]. The myosin VIIa protein contains a conserved N-terminal actin-binding and ATPase domain (motor domain), a neck region containing five isoleucine-glutamine (IQ) motifs, and a short predicted coiled-coil domain, followed closely by two myosin tail homology 4 (MyTH4) domains, two band 4.1-ezrin-radixin-moesin (FERM) domains, and an SH3 domain [18].…”
Section: Discussionmentioning
confidence: 99%
“…The myosin VIIa protein contains a conserved N-terminal actin-binding and ATPase domain (motor domain), a neck region containing five isoleucine-glutamine (IQ) motifs, and a short predicted coiled-coil domain, followed closely by two myosin tail homology 4 (MyTH4) domains, two band 4.1-ezrin-radixin-moesin (FERM) domains, and an SH3 domain [18]. The MYO7A gene has long been associated with Usher syndrome type 1B (USH1B), which is characterized by sensorineural HL, retinitis pigmentosa, and vestibular dysfunction [18,19]. In 1997, Weil et al [20] and Liu et al [21] have identified that MYO7A gene variants are associated with DFNB2.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, RP is confined to the eye, however, some 20-30% of patients are associated with non-ocular diseases like Usher's syndrome, which is associated with hearing impairment and is the most frequent form of syndromic RP [5]. The patients of RP typically lose night vision in adolescence, side vision in young adulthood, and central vision in later life because of the progressive loss of rod and cone photoreceptor cells.…”
mentioning
confidence: 99%